Education and Early Detection of Diabetes Mellitus Risk in North Jakarta Office Environment - Erlia Anggrainy Sianipar; Monica Fransiska; Marisa Felicia; Alnardo Tuamain; Monika Angelina; Maria Gracia Mutiara Misesha; Sherly Tandi Arrang (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
A low level of knowledge related to the causative factors, signs and symptoms, dangers, prevention, and treatment of diabetes mellitus (DM) causes an increasing number of DM sufferers worldwide, including in Indonesia. This community service activity aims to increase public knowledge, especially in the office environment, about DM disease and conduct early detection of DM. Participants in the community service activities consisted of 90 employees of an Accountant's office in North Jakarta. The community service activities included education about DM disease, tests of blood sugar, and question-and-answer discussions about DM. The results showed an increase in knowledge by 20.3% based on the score obtained from the pretest compared to the posttest. Based on the blood sugar test results, 98.9% of participants had blood sugar levels within normal limits, 1.1% were below average (hypoglycemia), and 1.1% were at risk of DM. This activity concludes that educational activities can increase participants' knowledge about DM disease, so it is hoped that the community can implement a healthy lifestyle to prevent DM disease and reduce the number of DM sufferers.